Cardiac tamponade as a rare presentation of Hodgkin’s lymphoma: a case report - Limanówka, Piotr; Kujawińska, Matylda; Kaput, Anna; Spyra, Aleksandra; Dobrakowski, Michał; Szczepański, Tomasz; Pobudejska-Pieniążek, Aneta (Frontiers in Oncology, 2025)
Hodgkin’s lymphoma usually manifests with symptoms such as enlarged peripheral lymph nodes, fever, night sweats, and weight loss. It’s the third most common pediatric cancer and includes two main types. Here, we describe a case of a 17-year-old boy, whose one of the first signs of Hodgkin’s lymphoma was cardiac tamponade. Moreover, our patient suffered from another episode of cardiac tamponade after proton beam therapy.